Inhibiting orofacial mimicry affects authenticity perception in vocal emotions - Vilaverde, R. F.; Horchak, O. V.; Pinheiro, A. P.; Scott, S. K.; Korb, S.; Lima, C. F. (Emotion, 2024)
Although emotional mimicry is ubiquitous in social interactions, its mechanisms and roles remain disputed. A prevalent view is that imitating others’ expressions facilitates emotional understanding, but the evidence is mixed and almost entirely based on facial emotions. In a preregistered study, we asked whether inhibiting orofacial mimicry affects authenticity perception in vocal emotions. Participants listened to authentic and posed laughs and cries, while holding a pen between the teeth and lips to inhibit orofacial responses (n = 75), or while responding freely without a pen (n = 75). They made authenticity judgments and rated how much they felt the conveyed emotions (emotional contagion). Mimicry inhibition decreased the accuracy of authenticity perception in laughter and crying, and in posed and authentic vocalizations. It did not affect contagion ratings, however, nor performance in a cognitive control task, ruling out the effort of holding the pen as an explanation for the decrements in authenticity perception. Laughter was more contagious than crying, and authentic vocalizations were more contagious than posed ones, regardless of whether mimicry was inhibited or not. These findings confirm the role of mimicry in emotional understanding and extend it to auditory emotions. They also imply that perceived emotional contagion can be unrelated to mimicry.